The Influence of Working Capital Financing, Micro Financing and Qardhul Hasan Funds on the Performance of Islamic Commercial Banks in Indonesia - Syahid, Muhammad; Elzaanin, Amina A.A; Noviarita, Heni; Kartika, Akbar Pratama; Noval, Muhammad (Jurnal Ilmiah Ekonomi Islam, 2024)
To maintain existence and competitiveness, various products are needed that can reach all levels of business needs. Working Capital Financing is intended for SME Retail to commercial scale, Micro Financing is intended for medium-sized MSMEs, while Qardhul Hasan financing is intended if lending lacks capital in the current contract. For this reason, this article wants to test how much influence Working Capital Financing and Micro Financing and with Qardhul Hasan Funds as moderating variables have on the Profitability of Islamic Banks in Indonesia. This study involved 14 Islamic Commercial Banks from 2019-2023 registered with the Financial Services Authority. The data was obtained from the OSIRIS website. The data analysis method used was multiple regression analysis. The hypothesis tests carried out were the F test, T test, and Adjusted R 2 determination coefficient. The results of the study simultaneously showed that independent variables had a significant effect on Islamic Bank Performance with a significance of 67%, this was because DQH was allocated to the productive sector and was included in the priority scale of superior customers. While partially PMK has a negative effect because it uses a profit sharing contract that is quite risky, and the PM and DQH variables have a positive effect on the performance of Islamic Banks, this is because PM uses a sale and purchase contract so that the risk is minimal and DQH uses the Qardhul hasan contract which is allocated to the productive sector so that the risk is minimal. The finding of this lending can be evaluated or converted with various products according to customer needs so that the performance of Islamic Banks can continue to increase as long as it does not deviate from Banking Quality Sharia which is its main mission.